(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2021)
Pollutants emitted from internal combustion engines cause significant environmental pollution, and the reduction of these pollutants is the goal of all. The deterioration of air quality is increasing year after year due to increasing the population and cars and low awareness of pollution reduction. In this study, the impact of recycling of exhaust gas in a spark ignition engine was tested on the NOx emitted from it, which is considered one of the most dangerous environmental pollutant. The results of the study showed that the brake specific fuel consumption increases by increasing the amount of the EGR interning the engine, also the brake thermal efficiency increases and the volumetric efficiency decreases with this increase. The NOx concentrations emitted are significantly reduced when high rates of EGR (15% and 20%) are added. The use of high octane fuel RON94.5 has helped to reduce the expected EGR damage, such as greater reduction in the specific fuel consumption, or a greater reduction in the volumetric efficiency.